Rancang Bangun Website Media Pembelajaran Di Smp Katolik Santa Maria Palangkaraya Dengan Php Mysql - Widiatry, Widiatry; Kristina, Dhea (Universitas Palangka Raya, 2022)
Santa Maria Catholic Middle School is a junior high school which is located at Jalan Cilik Riwut, Jekan Raya District, Palangka Raya City. It does not yet have a website like most schools in Palangkaraya City. So this Junior High School does not introduce its school to the wider community. Not only that, this junior high school also still uses the books offered by the teacher for its learning. Based on this background,